Estimating the value of carbon sequestration ecosystem services in the Mediterranean Sea: An ecological economics approach. (May 2015) - Melaku Canu, Donata; Ghermandi, Andrea; Nunes, Paulo A.L.D.; Lazzari, Paolo; Cossarini, Gianpiero; Solidoro, Cosimo
Highlights: We valuate carbon sequestration services in Mediterranean Sea marine ecosystems. The contribution of biological processes to carbon sequestration is always positive and ranges between 100 and 1500 million €/year for the Mediterranean Sea. The contribution of physical processes to carbon sequestration can be positive or negative, also depending on incoming Atlantic water. Our methodology can be applied elsewhere and produce result useful to populate a National System of Environmental and Economic Accounts. Values of carbon sequestration range from −135 to 1000 €/km 2 year; some exclusive economic zones are carbon sinks, others are carbon sources. Abstract: Ocean and marine ecosystems provide a range of valuable services to humans, including benefits such as carbon sequestration, whose economic value are as yet poorly understood. This paper presents a novel contribution to the valuation of carbon sequestration services in marine ecosystems with an application to the Mediterranean Sea. We combine a state-of-the-art biogeochemical model with various estimates of the social cost of carbon emissions to provide a spatially explicit characterization of the current flow of values that are attributable to the various sequestration processes, including the biological component. Using conservative estimates of the social cost of carbon, we evaluate the carbon sequestration value flows over the entire basin to range between 127 and 1722 million €/year. Values per unit area range from −135 to 1000 €/km 2 year, with the exclusive economic zone of some countries acting as net carbon sources. Whereas the contribution of physical processes can be either positive or negative, also depending on the properties of incoming Atlantic water, the contribution of biological processes to the marine "blue carbon" sequestration is always positive, and found to range between 100 to 1500 million €/year for the whole basin.